Habiter la nature en métropole : une hybridation ville-campagne par le jardin - Camille Robert-Boeuf; Julien Essers (Développement Durable et Territoires)
The city is undergoing major changes and sees the specialization of the urban spaces through metropolization. In this context, the place of urban peripheries is reconfigured and reinvented through the prism of new spatial relationships, new links between city and countryside. Using examples of Kazan (Russia) and Paris, we will show the role of gardens in the hybrid reconfiguration of ex-urban areas. Indeed, the various practices, representations and uses of the garden provide us with new analysis of urban-rural hybridization.